Acetonitrile Mediated Facile Synthesis and Self-Assembly of Silver Vanadate Nanowires into 3d Spongy-Like Structure as a Cathode Material for Lithium Ion Battery - Melo-Hurtado, F; Serafini, D; Casagrande-Denardin, J; Singh, D (Springer Netherlands, 2017)
We report the facile, one-step acetonitrile-mediated synthesis and self-assembly of β-AgVO3 nanowires into three-dimensional (3D) porous spongy-like hydrogel (~ 4 cm diameter) as cathode material for lithium ion battery of high performance and long-term stability. 3D structures made with superlong, very thin, and monoclinic β-AgVO3 nanowires exhibit high specific discharge capacities of 165 mAh g−1 in the first cycle and 100 mAh g−1 at the 50th cycle, with a cyclic capacity retention of 53% at a current density of 50 mA g−1. 3D structures are synthesized by reaction between ammonium vanadate and silver nitrate solution containing 5 mL of acetonitrile followed by a hydrothermal treatment at 200 °C for 12 h. Acetonitrile (used here for the first time in the silver vanadate synthesis) plays an important role in the self-assembly of the silver vanadate nanowires. A tentative growth mechanism for the 3D structure and lithium ions intercalation into β-AgVO3 nanowires has been discussed and described. © 2017, Springer Science+Business Media B.V.